Second thoughts about first principles in biology - Dustin Marshall; Craig White; Van Savage; Naomi Levine (Trends in Ecology & Evolution, 2026)

Second thoughts about first principles in biology - Dustin Marshall; Craig White; Van Savage; Naomi Levine (Trends in Ecology & Evolution, 2026)

New evidence for the Clactonian-Acheulean succession during MIS 11 from Devereux's Pit, Suffolk, UK - Rob Davis; Marcus Hatch; Simon G. Lewis; Claire Lucas; Simon O'Connor; Claire R.E. Harris; Joshua T. Hogue; Dylan Jones; Ellie Nelson; Simon A. Parfitt; Richard C. Preece; Kathryn M. Price; et al. (Quaternary Science Reviews, 2026)

Drivers and Consequences of Size Declines in Unicells - Dustin J. Marshall; Hayley E. Cameron; Akira Abe; Suzana Goncalves Leles; Craig R. White; John Delong (Ecology Letters, 2026)
The communities of unicellular microbes (bacteria, protists and yeasts) that underpin ecosystems are changing. In warmer conditions, protists tend to shrink, but the consequences of these changes in size are unclear. We show preliminary evidence that warming‐mediated declines in cell size observed in protists also apply to bacteria and yeasts. Predicting the consequences of these warming‐mediated size declines requires that the relationships between cell size and key functional traits are well‐characterised. We show that the critical relationship between unicellular size and energy use—that is, metabolic scaling—has been systematically mis‐estimated in the past. Projections of the effects of warming on unicellular respiration change from superlinear to sublinear once the metabolic scaling relationship is updated, with worrying consequences for the biological carbon pump and other ecosystem services. Other size‐function scaling relationships (e.g., photosynthesis) are likely to have been similarly mis‐estimated. Next, we show that theory on the relationships between size, temperature and demography is more ambivalent than previously recognised, leaving uncertainty as to how warming will alter the dynamics of unicellular populations. Finally, we identify pathways for improving our capacity to predict future changes in unicellular size, and decrease the uncertainty surrounding the consequences of these changes.

An aminostratigraphy of the northern Upper Rhine Graben, Germany - Ellie Nelson; Dustin White; Lucy Wheeler; Joachim Wedel; Christian Hoselmann; Heiner Heggemann; Wolfgang Rähle; Kirsty Penkman (Journal of Quaternary Science, 2025)
The northern Upper Rhine Graben (Germany) contains a complex, quasi‐continuous Quaternary record, but constraining its chronology is challenging. This study presents the first application of amino acid geochronology for this region using Bithynia opercula to establish a relative dating framework. Intra‐crystalline protein decomposition (IcPD) results from opercula have allowed their horizons to be statistically grouped into clusters of equivalent age. Independent chronological evidence associated with these clusters was evaluated to refine the sediment chronology. This framework both constrains the ages of key lithostratigraphic units and facilitates cross‐correlation of sediments across the graben, therefore providing a reference regional aminostratigraphy, which has also been extended to help constrain the age of nearby Palaeolithic sites. This approach shows the value of combining the multiparameter datasets from IcPD with other chronological evidence to cross‐correlate boreholes, hence creating a reference dataset for Quaternary deposits for a given region.

Predictive models to determine best strategy for metaphylaxis application in cattle at arrival to a feedyard - Lilli Heinen; Phillip A. Lancaster; Robert L. Larson; Dustin L. Pendell; Dannell J. Kopp; Brad J. White (Preventive Veterinary Medicine, 2025)

A Quaternary aminostratigraphy for the Pannonian Basin: The competing influences of time, burial depth and temperature in deep-core material - Ellie Nelson; Zoltán Püspöki; Dustin White; György Pogácsás; Richard William McIntosh; Bálint Szappanos; Lucy Wheeler; Tamás Fancsik; Kirsty Penkman (Quaternary Science Reviews, 2024)

Climatic and tectonic controls on deposition in the Heidelberg Basin, Upper Rhine Graben, Germany - Lukas Gegg; Laura Jacob; Olivier Moine; Ellie Nelson; Kirsty E.H. Penkman; Fiona Schwahn; Philipp Stojakowits; Dustin White; Ulrike Wielandt-Schuster; Frank Preusser (Quaternary Science Reviews, 2024)

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

Distal tephra reveal new MIS 5e Kos eruptions: Implications for the chronology and volcanic evolution histories in the Eastern Mediterranean region - Shuang Zhang; Simon Blockley; Simon J. Armitage; Chris Satow; Christina Manning; Omry Barzilai; Elisabetta Boaretto; Dustin White; Rhys Timms (Quaternary Science Reviews, 2023)

A Holocene floodplain sequence from the Kirenga Valley, Lake Baikal region (Siberia), and its significance for molluscan and mammalian biogeography - Dustin White; Simon A. Parfitt; Alexander A. Shchetnikov; Alexey S. Tesakov; Richard C. Preece (Quaternary International, 2023)

Avoiding growing pains in reproductive trait databases: the curse of dimensionality - Samuel C. Ginther; Hayley Cameron; Craig R. White; Dustin J. Marshall (Global Ecology and Biogeography, 2022)
Aim Reproductive output features prominently in many trait databases, but the metrics describing it vary and are often untethered to temporal and volumetric dimensions (e.g., fecundity per bout). The use of such ambiguous reproductive measures to make broad‐scale comparisons across taxonomic groups will be meaningful only if they show a 1:1 relationship with a reproductive measure that explicitly includes both a volumetric and a temporal component (i.e., reproductive mass per year). We sought to map the prevalence of ambiguous and explicit reproductive measures across taxa and to explore their relationships with one another to determine the cross‐compatibility and utility of reproductive metrics in trait databases. Location Global. Time period 1990–2021. Major taxa studied We searched for reproductive measures across all Metazoa and identified 19,785 vertebrate species (Chordata), and 440 invertebrate species (Arthropoda, Cnidaria or Mollusca). Methods We included 37 databases, from which we summarized the commonality of reproductive metrics across taxonomic groups. We also quantified scaling relationships between ambiguous reproductive traits (fecundity per bout, fecundity per year and reproductive mass per bout) and an explicit measure (reproductive mass per year) to assess their cross‐compatibility. Results Most species were missing at least one temporal or volumetric dimension of reproductive output, such that reproductive mass per year could be reconstructed for only 4,786 vertebrate species. Ambiguous reproductive measures were poor predictors of reproductive mass per year; in no instance did these measures scale at 1:1. Main conclusions Ambiguous measures systematically misestimate reproductive mass per year. Until more data are collected, we suggest that researchers should use the clade‐specific scaling relationships provided here to convert ambiguous reproductive measures to reproductive mass per year.

How does spawning frequency scale with body size in marine fishes? - Dustin J Marshall; Diego R Barneche; Craig R White (Fish and Fisheries, 2022)
How does fecundity scale with female size? Female size not only affects the number and size of offspring released in any one reproductive bout (i.e. batch fecundity) but also affects frequency of bouts that occur within a given spawning season (i.e. spawning frequency). Previous studies have noted contrasting effects of female size on spawning frequency such that the effect of female size on reproductive output and total egg production of a population remains unclear. If smaller females spawn more frequently, this could effectively nullify hyperallometry—the disproportionate contribution of larger females to batch fecundity. Here, we explore the relationship between female size and spawning frequency in marine fishes and test this relationship while controlling for phylogeny. Within all of the species considered, spawning frequency scaled positively with body size. Comparing across species, the smallest species showed steeper scaling than the largest. Considering only batch fecundity scaling probably underestimates the relationship between body size and absolute fecundity for many species; reproduction is likely to be more hyperallometric than is currently appreciated based on batch fecundity estimates. Second, an understanding of fecundity scaling depends on estimates of batch fecundity, spawning frequency and spawning duration—we have far more estimates of the first parameter than we do the others, and more studies are required.

Neanderthals on the Lower Danube: Middle Palaeolithic evidence in the Danube Gorges of the Balkans - Dušan Borić; Emanuela Cristiani; Rachel Hopkins; Jean‐Luc Schwenninger; Katarina Gerometta; Charly A. I. French; Giuseppina Mutri; Jelena Ćalić; Vesna Dimitrijević; Ana B. Marín‐Arroyo; Jennifer R. Jones; Rhiannon Stevens; et al. (Journal of Quaternary Science, 2022)
The article presents evidence about the Middle Palaeolithic and Middle to Upper Palaeolithic transition interval in the karst area of the Danube Gorges in the Lower Danube Basin. We review the extant data and present new evidence from two recently investigated sites found on the Serbian side of the Danube River – Tabula Traiana and Dubočka‐Kozja caves. The two sites have yielded layers dating to both the Middle and Upper Palaeolithic and have been investigated by the application of modern standards of excavation and recovery along with a suite of state‐of‐the‐art analytical procedures. The presentation focuses on micromorphological analyses of the caves’ sediments, characterisation of cryptotephra, a suite of new radiometric dates (accelerator mass spectrometry and optically stimulated luminescence) as well as proteomics (zooarchaeology by mass spectrometry) and stable isotope data in discerning patterns of human occupation of these locales over the long term.

Predicting the response of disease vectors to global change: The importance of allometric scaling - Louise S. Nørgaard; Mariana Álvarez‐Noriega; Elizabeth McGraw; Craig R. White; Dustin J. Marshall (Global Change Biology, 2022)
The distribution of disease vectors such as mosquitoes is changing. Climate change, invasions and vector control strategies all alter the distribution and abundance of mosquitoes. When disease vectors undergo a range shift, so do disease burdens. Predicting such shifts is a priority to adequately prepare for disease control. Accurate predictions of distributional changes depend on how factors such as temperature and competition affect mosquito life‐history traits, particularly body size and reproduction. Direct estimates of both body size and reproduction in mosquitoes are logistically challenging and time‐consuming, so the field has long relied upon linear (isometric) conversions between wing length (a convenient proxy of size) and reproductive output. These linear transformations underlie most models projecting species' distributions and competitive interactions between native and invasive disease vectors. Using a series of meta‐analyses, we show that the relationship between wing length and fecundity are nonlinear (hyperallometric) for most mosquito species. We show that whilst most models ignore reproductive hyperallometry (with respect to wing length), doing so introduces systematic biases into estimates of population growth. In particular, failing to account for reproductive hyperallometry overestimates the effects of temperature and underestimates the effects of competition. Assuming isometry also increases the potential to misestimate the efficacy of vector control strategies by underestimating the contribution of larger females in population replenishment. Finally, failing to account for reproductive hyperallometry and variation in body size can lead to qualitative errors via the counter‐intuitive effects of Jensen's inequality. For example, if mean sizes decrease, but variance increases, then reproductive outputs may actually increase. We suggest that future disease vector models incorporate hyperallometric relationships to more accurately predict changes in mosquito distribution in response to global change.

Linking life‐history theory and metabolic theory explains the offspring size‐temperature relationship - Amanda K. Pettersen; Craig R. White; Robert J. Bryson‐Richardson; Dustin J. Marshall (Ecology Letters, 2019)

Testing MacArthur's minimisation principle: do communities minimise energy wastage during succession? - Giulia Ghedini; Michel Loreau; Craig R. White; Dustin J. Marshall (Ecology Letters, 2018)
Robert MacArthur developed a theory of community assembly based on competition. By incorporating energy flow, MacArthur's theory allows for predictions of community function. A key prediction is that communities minimise energy wastage over time, but this minimisation is a trade‐off between two conflicting processes: exploiting food resources, and maintaining low metabolism and mortality. Despite its simplicity and elegance, MacArthur's principle has not been tested empirically despite having long fascinated theoreticians. We used a combination of field chronosequence experiments and laboratory assays to estimate how the energy wastage of a community changes during succession. We found that older successional stages wasted more energy in maintenance, but there was no clear pattern in how communities of different age exploited food resources. We identify several reasons for why MacArthur's original theory may need modification and new avenues to further explore community efficiency, an understudied component of ecosystem functioning.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Eco‐energetic consequences of evolutionary shifts in body size - Martino E. Malerba; Craig R. White; Dustin J. Marshall (Ecology Letters, 2018)
Size imposes physiological and ecological constraints upon all organisms. Theory abounds on how energy flux covaries with body size, yet causal links are often elusive. As a more direct way to assess the role of size, we used artificial selection to evolve the phytoplankton species Dunaliella tertiolecta towards smaller and larger body sizes. Within 100 generations ( c . 1 year), we generated a fourfold difference in cell volume among selected lineages. Large‐selected populations produced four times the energy than small‐selected populations of equivalent total biovolume, but at the cost of much higher volume‐specific respiration. These differences in energy utilisation between large (more productive) and small (more energy‐efficient) individuals were used to successfully predict ecological performance ( r and K ) across novel resource regimes. We show that body size determines the performance of a species by mediating its net energy flux, with worrying implications for current trends in size reduction and for global carbon cycles.

Does energy flux predict density‐dependence? An empirical field test - Giulia Ghedini; Craig R. White; Dustin J. Marshall (Ecology, 2017)
Changes in population density alter the availability, acquisition, and expenditure of resources by individuals, and consequently their contribution to the flux of energy in a system. While both negative and positive density‐dependence have been well studied in natural populations, we are yet to estimate the underlying energy flows that generate these patterns and the ambivalent effects of density make prediction difficult. Ultimately, density‐dependence should emerge from the effects of conspecifics on rates of energy intake (feeding) and expenditure (metabolism) at the organismal level, thus determining the discretionary energy available for growth. Using a model system of colonial marine invertebrates, we measured feeding and metabolic rates across a range of population densities to calculate how discretionary energy per colony changes with density and test whether this energy predicts observed patterns in organismal size across densities. We found that both feeding and metabolic rates decline with density but that feeding declines faster, and that this discrepancy is the source of density‐dependent reductions in individual growth. Importantly, we could predict the size of our focal organisms after eight weeks in the field based on our estimates of energy intake and expenditure. The effects of density on both energy intake and expenditure overwhelmed the effects of body size; even though higher density populations had smaller colonies (with higher mass‐specific biological rates), density effects meant that these smaller colonies had lower mass‐specific rates overall. Thus, to predict the contribution of organisms to the flux of energy in populations, it seems necessary not only to quantify how rates of energy intake and expenditure scale with body size, but also how they scale with density given that this ecological constraint can be a stronger driver of energy use than the physiological constraint of body size.

Phytoplankton size‐scaling of net‐energy flux across light and biomass gradients - Martino E. Malerba; Craig R. White; Dustin J. Marshall (Ecology, 2017)
Many studies examine how body size mediates energy use, but few investigate how size simultaneously regulates energy acquisition. Furthermore, rarely energy fluxes are examined while accounting for the role of biotic and abiotic factors in which they are nested. These limitations contribute to an incomplete understanding of how size affects the transfer of energy through individuals, populations, and communities. Here we characterized photosynthesis‐irradiance (P‐I) curves and per‐cell net‐energy use for 21 phytoplankton species spanning across four orders of magnitude of size and seven phyla, each measured across six light intensities and four population densities. We then used phylogenetic mixed models to quantify how body size influences the energy turnover rates of a species, and how this changes across environments. Rate‐parameters for the P‐I curve and net‐energy budgets were mostly highly correlated and consistent with an allometric size‐scaling exponent of interaction). The negative effect of population density on photosynthesis and respiration is mostly consistent with an active downregulation of metabolic rates following a decrease in per‐cell resource availability, possibly as an adaptive strategy to reduce the minimum requirements of a cell and improve its competitive ability. Also, because an increase in body size corresponds to a less‐than‐proportional increase in net‐energy (i.e. exponent

Do low oxygen environments facilitate marine invasions? Relative tolerance of native and invasive species to low oxygen conditions - Marcelo E. Lagos; Diego R. Barneche; Craig R. White; Dustin J. Marshall (Global Change Biology, 2017)
Biological invasions are one of the biggest threats to global biodiversity. Marine artificial structures are proliferating worldwide and provide a haven for marine invasive species. Such structures disrupt local hydrodynamics, which can lead to the formation of oxygen‐depleted microsites. The extent to which native fauna can cope with such low oxygen conditions, and whether invasive species, long associated with artificial structures in flow‐restricted habitats, have adapted to these conditions remains unclear. We measured water flow and oxygen availability in marinas and piers at the scales relevant to sessile marine invertebrates (mm). We then measured the capacity of invasive and native marine invertebrates to maintain metabolic rates under decreasing levels of oxygen using standard laboratory assays. We found that marinas reduce water flow relative to piers, and that local oxygen levels can be zero in low flow conditions. We also found that for species with erect growth forms, invasive species can tolerate much lower levels of oxygen relative to native species. Integrating the field and laboratory data showed that up to 30% of available microhabitats within low flow environments are physiologically stressful for native species, while only 18% of the same habitat is physiologically stressful for invasive species. These results suggest that invasive species have adapted to low oxygen habitats associated with manmade habitats, and artificial structures may be creating niche opportunities for invasive species.

Temperature effects on mass‐scaling exponents in colonial animals: a manipulative test - Diego R. Barneche; Craig R. White; Dustin J. Marshall (Ecology, 2017)
Body size and temperature are fundamental drivers of ecological processes because they determine metabolic rates at the individual level. Whether these drivers act independently on individual‐level metabolic rates remains uncertain. Most studies of intraspecific scaling of unitary organisms must rely on preexisting differences in size to examine its relationship with metabolic rate, thereby potentially confounding size‐correlated traits (e.g., age, nutrition) with size, which can affect metabolic rate. Here, we use a size manipulation approach to test whether metabolic mass scaling and temperature dependence interact in four species (two phyla) of colonial marine invertebrates. Size manipulation in colonial organisms allows tests of how ecological processes (e.g., predation) affect individual physiology and consequently population‐ and community‐level energy flux. Body mass and temperature interacted in two species, with one species exhibiting decreased and the other increased mass‐scaling exponents with increasing temperature. The allometric scaling of metabolic rate that we observe in three species contrasts with the isometric scaling of ingestion rates observed in some colonial marine invertebrates. Thus, we suggest that the often observed competitive superiority of colonial over unitary organisms may arise because the difference between energy intake and expenditure increases more strongly with size in colonial organisms.

Biofilm history and oxygen availability interact to affect habitat selection in a marine invertebrate - Marcelo E. Lagos; Craig R. White; Dustin J. Marshall (Biofouling, 2016)

Competition in benthic marine invertebrates: the unrecognized role of exploitative competition for oxygen - Nick Ferguson; Craig R. White; Dustin J. Marshall (Ecology, 2013)
Competition is a ubiquitous structuring force across systems, but different fields emphasize the role of different types of competition. In benthic marine environments, where some of the classic examples of competition were described, there is a strong emphasis on interference competition: marine invertebrates are assumed to compete fiercely for the limiting resource of space. Much of our understanding of the dynamics of this system is based on this assumption, yet empirical studies often find that increases in density can reduce performance despite free space being available. Furthermore, the assumption that space is the exclusively limiting resource raises paradoxes regarding species coexistence in this system. Here, we measure the availability of oxygen in the field and in the laboratory, as well as the tolerance of resident species to low‐oxygen conditions. We show that oxygen can be the primary limiting resource in some instances, and that exploitative competition for this resource is very likely among benthic marine invertebrates. Furthermore, growth form (and the associated risk of oxygen limitation) covaries with the ability to withstand oxygen‐poor conditions across a wide range of taxa. Oxygen availability at very small scales may influence the distribution and abundance of sessile marine invertebrates more than is currently appreciated. Furthermore, competition for multiple resources (space and oxygen) and trade‐offs in competitive ability for each may promote coexistence in this system.

A reassessment of late glacial – Holocene diatom oxygen isotope record from Lake Baikal using a geochemical mass‐balance approach - Anson W. Mackay; George E. A. Swann; Tim S. Brewer; Melanie J. Leng; David W. Morley; Natalia Piotrowska; Patrick Rioual; Dustin White (Journal of Quaternary Science, 2011)
We present a new palaeoenvironmental record of hydrological variability in Lake Baikal, based on re‐modelled δ 18 O diatom values of diatom silica (δ 18 O modelled ), where the residual contaminants are identified and compensated for using electron optical imaging and whole‐sample geochemistry. δ 18 O modelled interpretations are based on the balance between rivers with high δ 18 O values and rivers with low δ 18 O values. Isotopic variability is related to latitudinal differences in precipitation which feed these rivers. The δ 18 O modelled record suggests that rather moist conditions prevailed in the Lake Baikal region during the latter stages of the Younger Dryas. Throughout the Holocene, episodes of low δ 18 O modelled values are, in general, in good agreement with increases in percentage haematite‐stained grains in North Atlantic sediments (indicative of ice‐rafted debris events). Rivers with southerly catchments dominate fluvial input especially between c . 3.3 and 2 cal ka BP, concurrent with high precipitation in the Lake Baikal region. Copyright © 2011 John Wiley & Sons, Ltd.